2019
DOI: 10.1097/md.0000000000014011
|View full text |Cite
|
Sign up to set email alerts
|

Novel EZH2 mutation in a patient with secondary B-cell acute lymphocytic leukemia after deletion 5q myelodysplastic syndrome treated with lenalidomide

Abstract: Rationale:The gene deletion (5)(q22q35) is reported in 10–20% of myelodysplastic syndrome (MDS) cases and is associated with response to lenalidomide and favorable prognosis. The authors report here a clinical case of MDS transformation to B-cell acute lymphocytic leukemia (B-ALL) with an associated accrual of an additional mutation following treatment with lenalidomide.Patient Concerns:A 69-year-old man presented with progressive anemia, normal white blood cell count, and thrombocytopenia consistent with MDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… 8 The other studies revealed 2 cases of ALL after lenalidomide exposure to be positive for CD34 and CD79a. 9 - 11 The most consistent genetic abnormality found across studies is the 11q23 ( KMT2A ) rearrangement, followed by monosomies of chromosomes 5, 7, and/or 17, hypodiploidy. 12 This patient lacked the 11q23 (KMT2A) rearrangement and the monosomy of chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The other studies revealed 2 cases of ALL after lenalidomide exposure to be positive for CD34 and CD79a. 9 - 11 The most consistent genetic abnormality found across studies is the 11q23 ( KMT2A ) rearrangement, followed by monosomies of chromosomes 5, 7, and/or 17, hypodiploidy. 12 This patient lacked the 11q23 (KMT2A) rearrangement and the monosomy of chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional treatment regimens do not relieve their symptoms. The prognosis of MDS is related to many factors that are very complex [19]. Some studies have suggested that decitabine may be effective against high-risk MDS [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Although MDS transforms to AML often, it can also transform to other leukemias, including acute lymphocytic leukemia (ALL). The presence of del(5q) and mutations in TP53 or EZH2 are associated with the emergence of the ALL clone [ 79 ]. Deletion of the long arm of chromosome 20, too, is an occurrence in MDS and is detected at a frequency of 3–7%, often co-occurring with anemia and thrombocytopenia [ 80 , 81 ].…”
Section: Prognostic Systems For Mdsmentioning
confidence: 99%